(untitled) (Homoeopathy for All, 2024)
Warts, benign skin growths caused by the human papillomavirus (HPV), are a widespread dermatological condition affecting individuals worldwide. These growths are notably prevalent, with global estimates suggesting that around 10% of children and 1-5% of adults experience warts at some point in their lives. The frequency of warts varies by age, lifestyle, and environmental conditions. Children and adolescents, in particular, are at higher risk due to frequent skin to-skin contact in settings such as schools and sports. Additionally, regions with warm and humid climates often report higher rates of HPV transmission, contributing to increased wart prevalence.